Rotational cation dynamics in metal halide perovskites: Effect on phonons and material properties - Gallop,NP; Selig,O; Giubertoni,G; Bakker,HJ; Rezus,YLA; Frost,JM; Jansen,TLC; Lovrincic,R; Bakulin,AA (Journal of Physical Chemistry Letters, 2018)
The dynamics of organic cations in metal halide hybrid perovskites (MHPs) have been investigated using numerous experimental and computational techniques because of their suspected effects on the properties of MHPs. In this Perspective, we summarize and reconcile key findings and present new data to synthesize a unified understanding of the dynamics of the cations. We conclude that theory and experiment collectively paint a relatively complete picture of rotational dynamics within MHPs. This picture is then used to discuss the consequences of structural dynamics for electron–phonon interactions and their effect on material properties by providing a brief account of key studies that correlate cation dynamics with the dynamics of the inorganic sublattice and overall device properties.